2020
DOI: 10.1002/ange.201915401
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Matching versus Induced‐Fit Distortions: Binding Affinities of Planar and Curved Polyaromatic Hydrocarbons with a Tetragold Metallorectangle

Abstract: A tetragold(I) rectangle‐like metallocage containing two pyrene‐bis‐imidazolylidene ligands and two carbazolyl‐bis‐alkynyl linkers is used for the encapsulation of a series of polycyclic aromatic hydrocarbons (PAHs), including corannulene. The binding affinities obtained for the encapsulation of the planar PAHs guests in CD2Cl2 are found to exponentially increase with the number of π‐electrons of the guest (1.3 > logK >6.6). For the bowl‐shaped molecule of corannulene, the association constant is much lower th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 81 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…11 Catalysis of this bowl-to-bowl inversion has attracted considerable attention aer it was demonstrated that a cyclophane receptor catalyzes this process via induced-t catalysis. [12][13][14] It was later found that graphene (a planar twodimensional (2D) material composed of sp 2 -hybridized carbons) can also catalyze the bowl-to-bowl inversion in corannulene [15][16][17] as well as rotation and inversion reactions in related molecules. [18][19][20] It has also been demonstrated via extensive density functional theory (DFT) and ab initio calculations that these catalytic processes are driven by strong noncovalent interactions that typically exceed a hundred kJ mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Catalysis of this bowl-to-bowl inversion has attracted considerable attention aer it was demonstrated that a cyclophane receptor catalyzes this process via induced-t catalysis. [12][13][14] It was later found that graphene (a planar twodimensional (2D) material composed of sp 2 -hybridized carbons) can also catalyze the bowl-to-bowl inversion in corannulene [15][16][17] as well as rotation and inversion reactions in related molecules. [18][19][20] It has also been demonstrated via extensive density functional theory (DFT) and ab initio calculations that these catalytic processes are driven by strong noncovalent interactions that typically exceed a hundred kJ mol −1 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] It is worth mentioning, that alkynyl-gold (I) complexes with NHC ligands have shown interesting industrial applications as electroluminescent materials. [30][31][32][33] During the past three years we prepared a series of gold(I) metallotwezers [34][35][36][37][38] and metallocages [39][40] by combining the use of pyrene-functionalized NHCs and rigid bis-alkynyl linkers (Scheme 1). By doing so, we were able to obtain supramolecular systems that showed great ability to encapsulate polyaromatic aromatic hydrocarbons (PAHs).…”
Section: Introductionmentioning
confidence: 99%
“…By doing so, we were able to obtain supramolecular systems that showed great ability to encapsulate polyaromatic aromatic hydrocarbons (PAHs). [38][39][40] Some other metallosupramolecules showed a large ability to selfassociate in the presence of metal cations (Ag + , Cu + and Tl + ) forming interesting selfassociated structures [35,37] and polymers, [36] due to a combination of π−π-stacking and metallophilic interactions. These non-covalent interactions are known to play a very important role in the photophysical and catalytic [41][42] properties of metal complexes, as we recently observed for NHC complexes functionalized with rigid polyaromatic moieties.…”
Section: Introductionmentioning
confidence: 99%